2013
DOI: 10.1111/jan.12248
|View full text |Cite
|
Sign up to set email alerts
|

Getting psychosocial interventions into mental health nursing practice: a survey of skill use and perceived benefits to service users

Abstract: The findings indicate a requirement for nursing leadership to legitimize psychosocial interventions as core nursing work. For service users to experience this type of nursing, we propose the nomination of dedicated psychosocial intervention nurses to multidisciplinary teams. Support through guidelines, clinical supervision and audit by senior nurse managers is critical to implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
5
19
0
Order By: Relevance
“…Some participants expressed having incorporated new strategies and applying them both at work and in other everyday situations, feeling increasing power and not being dependent on external support. Studies have shown that relapses are less common after coping-developing interventions than after pharmacotherapy, indicating an empowering impact (34,35). However, as other participants felt the need for new support immediately after the intervention, it is not possible to expect everyone to be able to adopt new strategies in order to match the new, more complex demands in modern working life (36).…”
Section: Discussionmentioning
confidence: 95%
“…Some participants expressed having incorporated new strategies and applying them both at work and in other everyday situations, feeling increasing power and not being dependent on external support. Studies have shown that relapses are less common after coping-developing interventions than after pharmacotherapy, indicating an empowering impact (34,35). However, as other participants felt the need for new support immediately after the intervention, it is not possible to expect everyone to be able to adopt new strategies in order to match the new, more complex demands in modern working life (36).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Butler et al . () using a survey investigated the use of psychosocial interventions (by 58 mental health nurses in Ireland) following training and its perceived benefits to service users. There were statistically significant increases in the use of psychosocial interventions post‐training.…”
Section: Introductionmentioning
confidence: 99%
“…These authors (3)(4)15,(20)(21)(22) emphasize that the rehabilitation and recovery process of patients must take into account a psychosocial assessment, which consists on identifying sources of stress, social problems, and the need for specialized interventions. Other essential actions to meet mental health demands are drug management, referral to specialized services when necessary, group activities, lifestyle counseling, and working with families (3)(4)15,(20)(21)(22) . It is of utmost importance that teams help users maintain their independence and implement strategies to combat stigma and social isolation (9)(10)22) .…”
Section: Discussionmentioning
confidence: 99%